Hiatal hernia treatment: first robotic fundoplication in Uruguay - Muniz, Nicolás; Haro, Camila; Cubas, Santiago; Zeballos, Justino (Cirugía del Uruguay, 2025)
Surgical treatment of hiatal hernias is indicated when they are symptomatic or large to prevent acute complications. Surgery consists of hernia reduction, resection of the sac, and closure of the diaphragmatic crura, usually combined with an antireflux device. Watch the video on YouTube <a class="a_GcMg font-feature-liga-off font-feature-clig-off font-feature-calt-off text-decoration-underline text-strikethrough-none" draggable="false" href="https://www.youtube.com/watch?v=73goMUdo1u4" target="_blank" rel="noopener">https://www.youtube.com/watch?v=Y1hx4ZjyOkI&t=5s